Psychosocial Problems among Adolescent Students: An Exploratory Study in the Central Region of Nepal - Bista, Bihungum; Thapa, Pushpa; Sapkota, Diksha; Singh, Suman B.; Pokharel, Paras K. (Frontiers in Public Health, 2016)
Background: Recently, school has drawn attention, as one of the dominant factors for psychosocial development of students. Nepal, however has limited studies on this issue. Study sought to assess the prevalence of psychosocial problem among adolescent students and family related factors. Methods: Taking 787 adolescent students from 13 schools of Hetauda municipality, we accomplished a cross-sectional study. A set of structured questionnaire and Y-PSC (Youth-Pediatric Symptoms Checklist) was adopted. A series of univariate, bivarite and multivariate analysis were performed for statistical analysis. Results: One-fifth (17.03%) adolescent students suffered with psychosocial problem. Male (9.50%) got affected more, compared to their female counterparts (7.80%). Figure of psychosocial problem rose with rise in age group and class. Frequency of family dispute was significantly associated with psychosocial problem (95% CI: 2.27-17.23). Conclusion: Interventions on psychosocial problems need a greater start, with special emphasis on school setting, targeting adolescents and community settings, targeting parents.